Swiss Finance Banking, Finance, and Digitalization - Meier, Henri B.; Marthinsen, John E.; Gantenbein, Pascal A.; Weber, Samuel S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
(3z(BSwitzerland has always been a haven of stability and security. But the Swiss financial marketplace is in the midst of immense changes brought on by the changing global environment. Whether you are a Swiss banker or a Swiss banking client, this book will serve you as an indispensable companion and guide to the Finanzplatz Schweiz.(3y (B--Guy Spier, Value Invester, Switzerland This open access book provides a thorough explanation of Swiss financial markets and the banking secrecy rules for which this country has become known. It covers key topics, which are essential for practitioners and academics to understand about this powerhouse in world financial markets, in general, and private wealth administration, in particular. If there were an overriding goal, it would be to answer this question: (3z(BHow could a small country in the middle of Europe and surrounded by economic and financial giants, like Germany and France, develop financial marketsthat are globally competitive?(3y (BSwiss Finance explains the dramatic pressures brought to bear on the Swiss financial markets during past two decades, perhaps none of them so great as the competitive challenges caused by changes in Switzerland's banking secrecy laws and practices, as well the shifting tide of new wealth generation toward Asia (e.g., China, Singapore, and South Korea) and large emerging markets. In doing so, it separates myth from reality, providing an excellent basis for predicting future changes the nation will need to make in order to stay competitive. Henri B. Meier has been founder, Chairman or member of the Board of Directors of several venture capital companies, funds and foundations. Previously, he was member of the Roche Group Executive Committee and its Strategy Committee and for over 16 years Chief Financial Officer of the Roche group, and for 12 years a member of its Board. He also was founding Chairman of the Board of Directors of Givaudan AG as well as member of the Board of Directors of several Swiss Corporations. Before joining Roche, he was a member of the Executive Committee of Handelsbank National Westminster, responsible for the development of investment banking operations, member of the Executive Committee of Motor Columbus Ing. and Division Chief at the World Bank in Washington. John E. Marthinsen is Professor of Economics and International Business at Babson College in Babson Park, MA, where he holds The Distinguished Chair in Swiss Economics. Dr. Marthinsen earned his Ph.D. from the University of Connecticut in Storrs, where he was awarded Phi Beta Kappa and Phi Kappa Phi academic honors. Pascal Gantenbein, MRICS, is the Henri-B.-Meier professor of Financial Management at the University of Basel. He also serves as the Dean of Studies at University of Basel$1 (Bs Faculty of Business and Economics. His academic interests are in the areas of corporate finance and valuation, portfolio management and risk management, as well as real estate finance and venture capital. Samuel S. Weber is an independent wealth manager based in Zug, Switzerland. He studied business administration at the Universities of Basel and St. Gallen and has been working as an independent wealth manager since 2012. He is a passionate value investor, who is focused on investing in high-quality opportunities in the stock market with the aim of fostering productive investments in Switzerland and Europe. As a member of the Board of Trustees of the HBM Fondation, he is also committed to the professional development of young people and young adults.s
Chapter 1: Introduction -- Chapter 2: Finanzplatz Schweiz: Financial Center Switzerland -- Chapter 3: Swiss Banking System -- Chapter 4: Swiss Bank (Customer) Secrecy & the International Exchange of Information -- Chapter 5: Swiss Financial Market Regulators & Laws -- Chapter 6: Swiss Institutional Investors -- Chapter 7: Swiss National Bank & Swiss Franc's Role in Global Financial Markets -- Chapter 8: Swiss Debt Markets -- Chapter 9: Swiss Equity Markets -- Chapter 10: Swiss Derivative Markets -- Chapter 11: Financial Digitalization, Fintech, and the Collaborative Economy -- Chapter 12: Swiss Taxes on Investments and Financing -- Chapter 13: Summery & Outlook.
Keywords: Financial services industry; Capital market; Financial Services; Capital Markets